ANALISIS FAKTOR PENYEBAB MISKOMUNIKASI ANTARA KARYAWAN DI CLUB ROYAL HIDROFIT BANDUNG - Ageng Saepudin Kanda S; Nabila Rahma Yunita (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Communication is a basic human activity, by communicating humans can relate to each other both in daily life at home, at work and in the community environment. In the work environment there will always be problems, whether they are big problems or small problems. An example of a small thing is the miscommunication that occurred at Club Royal Hidrofit Bandung so it could cause big things. Miscommunication is often considered trivial by some employees.Miscommunication itself is something that basically you will often find in the workplace and other environments. Each individual certainly has a different character as well as the way each individual understands and conveys it. Often in everyday life there are misunderstandings in communication, from this misunderstanding various problems arise and the culmination is the emergence of conflict which leads to division. If this continues to happen, it will certainly make the situation in the workplace unconducive. Therefore, knowledge of good and correct communication is required. That way we can create & build effective, intense communication, thereby having a good influence on each other's communication habits & understanding.